Sensitivity of TATP to a TASER Electrical Output. Issue 6 (25th July 2014) - Gerber, Michael; Walsh, Graham; Hopmeier, Mike
Abstract A series of experiments were performed to evaluate and document the effect of a TASER ("stun gun") on triacetone triperoxide (TATP), an easily manufactured explosive used often in IEDs and suicide bombing vests. TATP samples were synthesized and subjected to several tests of their sensitivity. These samples were run through a BAM Friction test with a result of <0.5 N, Impact Test with a result of 5.8 ± 0.4 cm, and Electrostatic Discharge test with a result of 0.073 ± 0.018 J. In addition, TATP was shocked with a TASER in a variety of configurations. The TATP reacted in 17/17 tests when the TASER arced through the TATP and 0/4 times when the TATP was configured in such a way that the TATP was not subjected to the electrical arc. Based on the experimental data, TATP will readily explode in a variety of configurations by a TASER or similar device. Testing should be expanded, as the data presented here are limited to a single formulation of TATP. Just one of a large array of TASER‐like devices by a single manufacturer were tested; other devices, scenarios and formulations of TATP and other likely threat materials should be assessed.